2006
DOI: 10.1038/sj.jp.7211562
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Perinatal PTSD Questionnaire to enhance clinical utility

Abstract: Objective: To enhance the clinical utility of the Perinatal Post-Traumatic Stress Disorder (PTSD) Questionnaire (PPQ), the current study sought to refine the measure by changing the item response options from dichotomous choices to a likert scale format.Study Design: Using a convergent/divergent validity design and two data sources (traditional survey and World Wide Web), 58 high-risk and 86 low-risk mothers answered four questionnaires.Results: Principal components analysis of items on the modified PPQ reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 35 publications
2
121
1
4
Order By: Relevance
“…The association itself has defined a great amount of symptoms among which, the most common include sleep disorders (ex. nightmares), constant revival of the [14]. Furthermore, recent studies showed that those who suffered PTSD obtained irreversible changes in their brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association itself has defined a great amount of symptoms among which, the most common include sleep disorders (ex. nightmares), constant revival of the [14]. Furthermore, recent studies showed that those who suffered PTSD obtained irreversible changes in their brain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies showed that those who suffered PTSD obtained irreversible changes in their brain. They had increased epinephrine, norepinephrine, 14 Fig. 2 The correlation of labor duration with first breastfeeding testosterone, cortisol levels and increased thyroxin function [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of the infant's medical complications were found to be predictive of maternal PTSD symptoms. 16 In a series of studies from the University of North Carolina, investigators surveyed various cohorts of mothers of premature infants requiring mechanical ventilation, premature infants classified as VLBW, medically fragile infants (defined as requiring hospitalization for a life-threatening illness) and infants seropositive for HIV. [17][18][19][20] Nearly one-fifth of the mothers of premature infants and those of HIV-positive infants were at serious risk for depression, even approaching 2 years after delivery.…”
Section: Physical Healthmentioning
confidence: 99%
“…Previous studies have used various instruments to evaluate postnatal stress symptoms, including the Posttraumatic Stress Disorder Questionnaire (PTSD-Q), the Impact Event Scale -Revised (IES-R), the Posttraumatic Stress Symptoms-Self Report (PSS-SR), the Traumatic Event Scale (TES), and the Perinatal Posttraumatic Stress Disorder Questionnaire (PPQ) [4][5][6][14][15][16][17]. However, these existing scales cannot accurately measure postnatal stress symptoms related to childbirth.…”
Section: Introductionmentioning
confidence: 99%